2020
DOI: 10.3389/fcell.2020.00183
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Kidney Development: From the Embryo to the Kidney Organoid

Abstract: Development of the metanephric kidney is strongly dependent on complex signaling pathways and cell-cell communication between at least four major progenitor cell populations (ureteric bud, nephron, stromal, and endothelial progenitors) in the nephrogenic zone. In recent years, the improvement of human-PSC-derived kidney organoids has opened new avenues of research on kidney development, physiology, and diseases. Moreover, the kidney organoids provide a three-dimensional (3D) in vitro model for the study of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 179 publications
(223 reference statements)
0
37
0
Order By: Relevance
“…Furthermore, in vitro-generated human pluripotent stem cell (hPSC)-derived kidney cells provide a suitable platform for studying kidney development, physiology, disease modeling, and drug screening. Although hPSCsderived kidney organoids express some markers of fully differentiated kidney tissues, they have relatively immature characteristics [2]. Several strategies have been reported to improve the maturity of in vitro-differentiated kidney structures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, in vitro-generated human pluripotent stem cell (hPSC)-derived kidney cells provide a suitable platform for studying kidney development, physiology, disease modeling, and drug screening. Although hPSCsderived kidney organoids express some markers of fully differentiated kidney tissues, they have relatively immature characteristics [2]. Several strategies have been reported to improve the maturity of in vitro-differentiated kidney structures.…”
Section: Introductionmentioning
confidence: 99%
“…Embryological studies demonstrated that spatiotemporal cell-cell communication and signals from the complex microenvironment during development have important roles in the proper maintenance and differentiation of renal cells. PSC-derived renal cells can be generated following the same developmental events that occur during the embryonic period [2]. In recent years, multistep protocols have been used for differentiation of hPSCs into the renal lineage by recapitulating stages of in vivo kidney development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the kidney, more than a dozen distinct cell types contribute to the structure and function of the nephron in vivo. The reconstitution of a nephron would necessitate direct reprogramming to a common ancestor of all contributing cell types, namely, nephron progenitor cells, endothelial progenitor cells, and stromal progenitor cells [19]. The required approach to developing tissue akin to the native kidney is directed differentiation, a method predicated upon profound knowledge of kidney development.…”
Section: Introductionmentioning
confidence: 99%